Ghrelin and NUCB2/Nesfatin-1 expression in unilateral testicular torsion-induced rats with and without N-acetylcysteine - Sarac, M.; Bakal, U.; Tartar, T.; Kuloglu, T.; Yardim, M.; Artas, G.; Kazez, A. (C M B Assoc, 2017)
Testicular torsion (TT) is a common urological problem in the field of pediatric surgery. The degree and duration of torsion determines the degree of testicular damage; however, its effects on the expression of octanoylated ghrelin and nucleobindin 2 (NUCB2)/nesfatin-1 synthetized from testicular tissue remain unclear. We explored the effects of experimentally induced unilateral TT on serum and contralateral testicular tissue ghrelin and NUCB2/nesfatin-1 levels, and determined whether N-acetyl cysteine (NAS) treatment had any effects on their expression. A total of 42 Wistar Albino strain rats were divided into 7 groups: Group (G) I control, GII sham, GIII 12-hour torsion, GIV 12-hour torsion + detorsion + 100 mg/kg NAS, GV 24-hour torsion, GVI 24-hour torsion + detorsion + 100 mg/kg NAS, and GVII 100 mg/kg NAS. Octanoylated ghrelin and NUCB2/nesfatin-1 concentrations were evaluated in serum using the ELISA method and in testicular tissue with immunohistochemical methods. Immunoreactivity of octanoylated ghrelin significantly increased in GI compared to GIII, GV, and GVI (p<0.05). NUCB2/nesfatin-1 immunoreactivity increased in GV and GVIII relative to GI (p<0.05). In the 12-hour torsion group, a significant decrease in octanoylated ghrelin levels with NAS treatment was observed; however, in the 24-hour torsion group, a significant decrease was not observed. In the 12-hour torsion + NAS treatment group, a significant change was not observed in NUCB2/nesfatin-1 expression. Following 24-hour torsion, an increase in NUCB2/nesfatin-1 levels was observed, and NAS treatment did not reverse this increase. It was determined that increases in the expression of octanoylated ghrelin and NUCB2/nesfatin-1, the latter of which was a result of TT, reflect damage in this tissue. Importantly, NAS treatment could prevent this damage. Thus, there may be a clinical application for the combined use of NAS and octanoylated ghrelin in preventing TT-related infertility.
Keywords: Testicular torsion; Octanoylated ghrelin; NUCB2/nesfatin-1; N-acetylcysteine; Rat